A new species of Atractodenchelys (Synaphobranchidae, Anguilliformes) from Vietnam - van Vo, Quang; Ho, Hsuan-Ching (Zootaxa, 2020)
A new species of the synaphobranchid genus Atractodenchelys is described based on 31 specimens collected off Quy Nhon and Nha Trang, southern Vietnam. The new species can be distinguished from the only two congeners in the genus by having much fewer total vertebrae (155‒158, vs. 168‒172 in A. phrix and 186‒199 in A. robinsorum), a relatively long head (head length 10.1‒12.3% TL), a relatively short snout (30.0‒35.8% HL), head longer than trunk length (vs. about equal in length in both species); and 5‒6 compound teeth on vomer (vs. 7‒8 in A. robinsorum).